Laboratory Investigation of the Effect of Particle and Vegetation Roughness on Changes in Drag Force in an Open Channel - Salahi, Kimiya; Ahadiyan, Javad; Zeng, Yu-hong; Nadian, Hossein Azizi; Sajjadi, Mohsen (Journal of Environmental Accounting and Management, 2026)
The main goal of the current research was to investigate the effect of particle and vegetation roughness arrangement on changes in the drag force in an open channel in different configurations, flow rates, and water depths. Therefore, a series of experiments were conducted in a flume with a length of 3.8 meters, a width of 0.8 meters, and a height of 0.55 meters located in the hydraulic laboratory of the Shahid Chamran University of Ahvaz. Drag forces were obtained for each test. The results of the tests showed the increase in the flow rate in most of the tests directly affected the amount of drag force. On average, at 15 L/s discharge, with an increase in depth from 10 to 20 cm, the momentum absorption can reach 60% for the particles’ roughness. While the same conditions have occurred for vegetation roughness, the momentum absorption is less than 30%. The results provided effective results to know the performance of different arrangements in the scope of this research.